Preparation method of crystal-level potassium decafluoroterbium acid
Through multi -step process to prepare potassium hyperthyll pyrite, it solves the problem of industrialization preparation methods that lack crystal grade tenfluorosate, and realize the preparation of high -purity and low impurities to meet the needs of industrial applications.
Patent Information
- Application Number
- CN202411489946.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
There is no disclosed industrial preparation method for crystal-grade potassium decafluoride in China, which leads to the preparation problems of this material in industrial applications.
A multi-step process is adopted, including the preparation of high-purity terbium carbonate, preparation of high-purity terbium trifluoride, and through reaction with high-purity potassium hydrogen fluoride, after multiple drying and high-temperature reactions, potassium decafluoroteblate is finally produced. This method ensures high purity and low impurity content of the product by strictly controlling reaction conditions and using high-purity materials.
The content of cobalt, nickel, copper, titanium, titanium, titanium, cadmium, cadmium, chromium content is less than 0.5 ppm, iron is less than 1ppm, oxygen <0.02 %, and potassium of more than 99.99 % of the purity can meet the crystal grade tenfluoro fluoride. The requirements of potassium hydraulite.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing potassium terbium decafluoroate. Background Art
[0002] The active ions used in laser crystals are mainly transition metal ions and trivalent rare earth ions. The optical electrons of transition metal ions are 3d electrons in the outer layer. In the crystal, this optical electron is susceptible to the direct effect of the surrounding crystal field, so the spectral characteristics of crystals of different structural types are very different. The 4f electrons of trivalent rare earth ions are shielded by the 5s and 5p outer electrons, which weakens the effect of the crystal field on them, but the perturbation of the crystal field makes the originally forbidden 4f electron transition possible, producing narrow-band absorption and fluorescence spectra. Therefore, the spectrum of trivalent rare earth ions in different crystals does not change as much as that of transition metal ions. The matrix crystals used in laser crystals are mainly oxides and fluorides. Potassium decafluoroterbium phosphate is a laser crystal with excellent properties after crystal pulling, and has good prospects. However, there is currently no public industrial preparation method for crystal-grade potassium decafluoroterbium phosphate in China. Summary of the invention
[0003] In order to solve the technical problem that there is currently a lack of an industrialized preparation method for crystalline potassium decafluoroterbium oxide in China, the present invention provides a preparation method for crystalline potassium decafluoroterbium oxide.
[0004] The technical solution of the present invention is:
[0005] A method for preparing crystalline potassium decafluoroterbium oxide, which is special in that it comprises the following steps:
[0006] Step 1, preparing high-purity terbium carbonate;
[0007] Step 1.1: dissolving high-purity hydrated terbium nitrate crystals with high-purity water to form a terbium nitrate solution with a specific gravity of 1.15-1.2, adding the solution to a pure ammonium carbonate solution, adjusting the pH to 8-9, heating to above 80° C. (stirring and aging above this temperature can reduce the bound water in the molecule, facilitating production operations), stirring and reacting for 1-2 hours to obtain a high-purity terbium carbonate synthetic solution; the high-purity hydrated terbium nitrate crystals are hydrated nitric acid with iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents all less than 0.2 ppm Terbium crystals; the pure ammonium carbonate solution is an ammonium carbonate solution that does not contain mechanical impurities and trace insolubles, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all less than 0.1ppm; in this step, the high-purity hydrated terbium nitrate crystals are dissolved in high-purity water to a specific gravity of 1.15-1.2 because too small a specific gravity will lead to too low a production capacity, and too large a specific gravity will form a hydrate and cannot be operated; the pH value is adjusted to 8-9 because if the pH value is not within this range, the yield of terbium salt will be low.
[0008] Step 1.2: centrifuging the high-purity terbium carbonate synthesis solution while hot, washing with water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0009] Step 2, preparing high-purity terbium trifluoride;
[0010] Using electronic grade hydrofluoric acid and the high-purity terbium carbonate to carry out a heat-insulating stirring reaction to drive out carbonate ions to obtain a terbium trifluoride synthetic liquid, and then centrifuging to obtain a terbium trifluoride filter cake;
[0011] Step 3, synthesizing potassium terbium decafluoroate;
[0012] Step 3.1: adding the terbium trifluoride filter cake to a high-purity potassium bifluoride solution, stirring evenly, heating to 120-150° C. and evaporating to dryness to obtain a mixed crystal of potassium bifluoride and terbium trifluoride;
[0013] Step 3.2: Dry the potassium bifluoride and terbium trifluoride mixed crystal at 200-250°C for 3-4 hours, then dry at 500-550°C for 1-2 hours under nitrogen protection, fully dehydrate and fluorinate, and finally heat to 1100-1200°C for 2-3 hours to remove excess fluoride ions to obtain a finished product of potassium decafluoroterbium oxide. The sample was sent to the Chinese Academy of Sciences for testing, and the test data showed that the contents of cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium were all less than 0.5ppm, iron was less than 1ppm, oxygen was less than 0.02%, and the purity was more than 99.99%, meeting the requirements of crystalline-grade potassium decafluoroterbium oxide.
[0014] Step 3 involves four temperature ranges in total. The first temperature range of 120-150°C is a temperature that steam can reach, so it can be evaporated in a steam drying box; the second temperature range of 200-250°C can achieve full reaction at a temperature where potassium bifluoride decomposes relatively slowly, while removing most of the water. If the temperature is too high, potassium bifluoride will decompose too quickly, and effective reaction components will be lost, and certain hydrolysis or oxidation problems will also occur; the third temperature range of 500-550°C is to remove most of the excess water and hydrogen fluoride in potassium bifluoride and prevent hydrolysis and oxidation; the fourth temperature range of 1100-1200°C is to ensure that fluoride ions and water are completely removed, and other unknown high-boiling impurities are volatilized to ensure product purity.
[0015] Furthermore, the preparation method of high-purity hydrated terbium nitrate crystals in step 1.1 is specifically as follows:
[0016] First, analytical pure nitric acid is added to a reaction kettle, and then water is added to dilute it in a ratio of 1:1, and then high-purity 4N terbium oxide is slowly added thereto, the molar ratio of nitric acid to terbium is 3:1, the pH is adjusted to 1-2, the temperature is raised to 60-70°C, the reaction is stirred for 30-60 minutes, and the supernatant is filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution;
[0017] Then, the terbium nitrate solution is heated to 110-120° C., concentrated under slight negative pressure (the slight negative pressure here refers to the negative pressure amount that the negative pressure gauge slightly swings and the value cannot be read), and after a large amount of crystals are concentrated, the solution is stirred and cooled to 20-30° C. (the crystallization yield will be reduced if the temperature is higher than this temperature, and additional refrigeration equipment is required if the temperature is lower than this temperature, which increases the cost), the crystals are fished out, and dried with a centrifuge, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0018] Furthermore, the preparation method of the pure ammonium carbonate solution in step 1.1 is specifically as follows:
[0019] Reagent-grade ammonium carbonate is dissolved in high-purity water to a mass fraction of 15-20%, and filtered to remove mechanical impurities and trace insolubles. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution are controlled to be less than 0.1 ppm to obtain a pure ammonium carbonate solution.
[0020] Optimally, reagent-grade ammonium carbonate is dissolved to a mass fraction of 20%. On the one hand, if the mass fraction is too large, a lot of smoke will appear, which is difficult to operate. At the same time, the concentration of terbium carbonate prepared later will be too high and the viscosity will be too high, which is difficult to operate. On the other hand, if the mass fraction is too small, the production capacity will be reduced.
[0021] Furthermore, in step 1.2, 800 mesh filter cloth is used and centrifugation is performed at a speed of 1000 rpm.
[0022] Furthermore, step 2 is specifically as follows:
[0023] Step 2.1 Add 40-50% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 60-80° C., add the high-purity terbium carbonate obtained in step 1.2, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1-2, heat it to 80° C., stir and react for 2-3 hours to drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0024] Step 2.2: The terbium trifluoride synthesis solution is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth to obtain a terbium trifluoride filter cake.
[0025] Furthermore, the step 3.1 is specifically as follows:
[0026] Step 3.1.1 Add electronic grade hydrofluoric acid into a tetrafluoroethylene beaker, then add pure water to dilute it to a mass fraction of 20-30%, add high-purity potassium hydroxide, the molar ratio of hydrofluoric acid to potassium hydroxide is 2:1, and obtain a potassium bifluoride solution; the high-purity potassium hydroxide here refers to an index better than or equal to premium grade purity.
[0027] Step 3.1.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the potassium bifluoride solution obtained in step 3.1.1, wherein the molar ratio of potassium bifluoride to terbium trifluoride is 1:3; stirring evenly; heating to 120-150° C. for evaporation to obtain a potassium bifluoride terbium trifluoride mixed crystal.
[0028] The present invention also provides a crystalline potassium decafluoroterbium oxide, which is special in that it is prepared by the above method.
[0029] The advantages of the present invention are:
[0030] The invention can industrially produce potassium decafluoroterbium oxide with the contents of cobalt, nickel, copper, titanium, vanadium, cadmium and chromium all less than 0.5 ppm, iron less than 1 ppm, oxygen less than 0.02% and a purity of more than 99.99%, thus meeting the requirements of crystalline-grade potassium decafluoroterbium oxide. DETAILED DESCRIPTION
[0031] The present invention is conceived as follows:
[0032] The main difficulty in preparing crystal-grade materials is how to reduce the oxygen content. In order to solve this problem, the present invention uses potassium bifluoride in the process of adding potassium. The excess hydrogen fluoride can play a role in preventing hydrolysis and oxidation during the drying process. At the same time, high-purity nitrogen protection is used to carry out high-temperature reaction to prevent oxidation, so that the oxygen content of the potassium decafluoroterbium oxide product finally prepared meets the requirements of crystal-grade materials.
[0033] In addition, potassium decafluoroterbium oxide is a mixed crystal of terbium fluoride and potassium fluoride, which needs to be mixed very evenly. Therefore, the present invention can ensure the uniformity of the mixture by liquid phase evaporation, crystallization and mixing.
[0034] The reaction equation involved in the present invention is:
[0035] 2Tb(NO3)3+3(NH4)2CO3=====Tb2(CO3)3+6NH4NO3
[0036] Tb2(CO3)3+6HF====2TbF3+3H2O+3CO2
[0037] 3TbF3+KHF2====KTb3F 10 +HF
[0038] The present invention is further described in detail below by way of examples.
[0039] Example 1
[0040] In this embodiment, crystalline potassium decafluoroterbium oxide is prepared by the following steps:
[0041] Step 1, preparing high-purity terbium carbonate;
[0042] Step 1.1: terbium salt purification;
[0043] First, analytical pure nitric acid was added to the reactor, and then pure water was added in a ratio of 1:1 to dilute it by half. Then, high-purity 4N terbium oxide was slowly added thereto, and the molar ratio of nitric acid to terbium was 3:1. The pH was adjusted to 1, the temperature was raised to 60°C, and the reaction was stirred for 60 minutes. The supernatant was filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution.
[0044] Then, the terbium nitrate solution is heated to 110° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 20° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0045] Step 1.2 ammonium carbonate purification;
[0046] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 20%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0047] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.16, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 8, heating to above 80° C., stirring and reacting for 1 hour, and obtaining a high-purity terbium carbonate synthetic solution;
[0048] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0049] Step 2, preparing high-purity terbium trifluoride;
[0050] Step 2.1 Add 50% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 60° C., add the high-purity terbium carbonate obtained in step 1.4, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1, heat it to 80° C., stir and react for 2 hours to drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0051] Step 2.2: The terbium trifluoride synthesis solution is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth to obtain a terbium trifluoride filter cake;
[0052] Step 3, synthesizing potassium terbium decafluoroate;
[0053] Step 3.1: adding electronic grade hydrofluoric acid to a tetrafluoroethylene beaker, and then adding pure water to dilute to a mass fraction of 25%, and then adding high-purity potassium hydroxide thereto, the molar ratio of hydrofluoric acid to potassium hydroxide being 2:1, to obtain a potassium bifluoride solution;
[0054] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the potassium bifluoride solution obtained in step 3.1, wherein the molar ratio of potassium bifluoride to terbium trifluoride is 1:3, stirring evenly, heating to 120° C. and evaporating to dryness to obtain a mixed crystal of potassium bifluoride and terbium trifluoride;
[0055] Step 3.3: Add the potassium bifluoride and terbium trifluoride mixed crystal obtained in step 3.2 to an iridium crucible, dry at 200°C for 4 hours, then add to a tubular furnace and dry at 550°C for 1 hour under nitrogen protection, fully dehydrate and fluorinate, and finally heat to 1200°C for 2 hours, and perform high temperature reaction under nitrogen protection to remove excess fluoride ions to obtain a finished product of potassium decafluoroterbium oxide. The sample was sent to the Chinese Academy of Sciences for testing, and the test data showed that cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium were all less than 0.5ppm, iron was less than 1ppm, oxygen was less than 0.02%, and the purity reached more than 99.99%, meeting the requirements of crystalline potassium decafluoroterbium oxide.
[0056] Example 2
[0057] In this embodiment, crystalline potassium decafluoroterbium oxide is prepared by the following steps:
[0058] Step 1, preparing high-purity terbium carbonate;
[0059] Step 1.1: terbium salt purification;
[0060] First, analytical pure nitric acid is added to the reactor, and then pure water is added in a 1:1 ratio to dilute it by half, and then high-purity 4N terbium oxide is slowly added thereto, the molar ratio of nitric acid to terbium is 3:1, the pH is adjusted to 1.3, the temperature is raised to 70°C, and the reaction is stirred for 60 minutes, and the supernatant is filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution;
[0061] Then, the terbium nitrate solution is heated to 120° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 25° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0062] Step 1.2 ammonium carbonate purification;
[0063] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 20%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0064] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.18, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 8.6, heating to above 80° C., stirring and reacting for 1.5 hours to obtain a high-purity terbium carbonate synthetic solution;
[0065] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0066] Step 2, preparing high-purity terbium trifluoride;
[0067] Step 2.1 Add 50% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 70° C., add the high-purity terbium carbonate obtained in step 1.4, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1.3, heat it to 80° C., keep it warm and stir it for 2.5 hours, drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0068] Step 2.2: The terbium trifluoride synthesis solution is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth to obtain a terbium trifluoride filter cake;
[0069] Step 3, synthesizing potassium terbium decafluoroate;
[0070] Step 3.1: adding electronic grade hydrofluoric acid to a tetrafluoroethylene beaker, and then adding pure water to dilute to a mass fraction of 25%, and then adding high-purity potassium hydroxide thereto, the molar ratio of hydrofluoric acid to potassium hydroxide being 2:1, to obtain a potassium bifluoride solution;
[0071] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the potassium bifluoride solution obtained in step 3.1, wherein the molar ratio of potassium bifluoride to terbium trifluoride is 1:3, stirring evenly, heating to 130° C. and evaporating to dryness to obtain a mixed crystal of potassium bifluoride and terbium trifluoride;
[0072] Step 3.3: Add the potassium bifluoride and terbium trifluoride mixed crystal obtained in step 3.2 to an iridium crucible, dry at 250°C for 3 hours, then add to a tubular furnace and dry at 500°C for 2 hours under nitrogen protection, fully dehydrate and fluorinate, and finally heat to 1100°C for 3 hours, and perform high temperature reaction under nitrogen protection to remove excess fluoride ions to obtain a finished product of potassium decafluoroterbium oxide. The sample was sent to the Chinese Academy of Sciences for testing, and the test data showed that cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium were all less than 0.5ppm, iron was less than 1ppm, oxygen was less than 0.02%, and the purity reached more than 99.99%, meeting the requirements of crystalline potassium decafluoroterbium oxide.
[0073] Example 3
[0074] In this embodiment, crystalline potassium decafluoroterbium oxide is prepared by the following steps:
[0075] Step 1, preparing high-purity terbium carbonate;
[0076] Step 1.1: terbium salt purification;
[0077] First, analytical pure nitric acid was added to the reactor, and then pure water was added in a 1:1 ratio to dilute it by half. Then, high-purity 4N terbium oxide was slowly added thereto, and the molar ratio of nitric acid to terbium was 3:1. The pH was adjusted to 1.3, the temperature was raised to 70°C, and the reaction was stirred for 45 minutes. The supernatant was filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution.
[0078] Then, the terbium nitrate solution is heated to 120° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 25° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0079] Step 1.2 ammonium carbonate purification;
[0080] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 15%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0081] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.2, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 8.3, heating to above 80° C., stirring and reacting for 2 hours to obtain a high-purity terbium carbonate synthetic solution;
[0082] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0083] Step 2, preparing high-purity terbium trifluoride;
[0084] Step 2.1 Add 40% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 75° C., add the high-purity terbium carbonate obtained in step 1.4 thereto, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1.3, heat it to 80° C., stir and react for 3 hours to remove the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0085] Step 2.2: The terbium trifluoride synthesis solution is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth to obtain a terbium trifluoride filter cake;
[0086] Step 3, synthesizing potassium terbium decafluoroate;
[0087] Step 3.1: adding electronic grade hydrofluoric acid to a tetrafluoroethylene beaker, and then adding pure water to dilute to a mass fraction of 20%, and then adding high-purity potassium hydroxide thereto, the molar ratio of hydrofluoric acid to potassium hydroxide being 2:1, to obtain a potassium bifluoride solution;
[0088] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the potassium bifluoride solution obtained in step 3.1, wherein the molar ratio of potassium bifluoride to terbium trifluoride is 1:3, stirring evenly, heating to 150° C. and evaporating to dryness to obtain a mixed crystal of potassium bifluoride and terbium trifluoride;
[0089] Step 3.3: Add the potassium bifluoride and terbium trifluoride mixed crystal obtained in step 3.2 to an iridium crucible, dry at 250°C for 3.5 hours, then add to a tubular furnace and dry at 530°C for 1.5 hours under nitrogen protection, fully dehydrate and fluorinate, and finally heat to 1200°C for 2 hours, and perform high temperature reaction under nitrogen protection to remove excess fluoride ions to obtain a finished product of potassium decafluoroterbium oxide. The sample was sent to the Chinese Academy of Sciences for testing, and the test data showed that cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium were all less than 0.5ppm, iron was less than 1ppm, oxygen was less than 0.02%, and the purity reached more than 99.99%, meeting the requirements of crystalline potassium decafluoroterbium oxide.
[0090] Example 4
[0091] In this embodiment, crystalline potassium decafluoroterbium oxide is prepared by the following steps:
[0092] Step 1, preparing high-purity terbium carbonate;
[0093] Step 1.1: terbium salt purification;
[0094] First, analytical pure nitric acid was added to the reactor, and then pure water was added in a ratio of 1:1 to dilute it by half. Then, high-purity 4N terbium oxide was slowly added thereto, and the molar ratio of nitric acid to terbium was 3:1. The pH was adjusted to 2, the temperature was raised to 65°C, and the reaction was stirred for 30 minutes. The supernatant was filtered using a filter element with a filtration accuracy of 1 μm to obtain a terbium nitrate solution.
[0095] Then, the terbium nitrate solution is heated to 115° C. and concentrated under a slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 30° C., the crystals are fished out and dried with a centrifuge. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
[0096] Step 1.2 ammonium carbonate purification;
[0097] Add reagent grade ammonium carbonate into high-purity water and dissolve it to a mass fraction of 18%, and filter it with a filter element with a filtration accuracy of 1 μm to remove mechanical impurities and trace insoluble matter. The content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution is controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained;
[0098] Step 1.3: dissolving the hydrated terbium nitrate crystals obtained in step 1.1 into a terbium nitrate solution with a specific gravity of 1.15, adding the terbium nitrate solution to the ammonium carbonate solution obtained in step 1.2, adjusting the pH to 9, heating to above 80° C., stirring and reacting for 1 hour, and obtaining a high-purity terbium carbonate synthetic solution;
[0099] Step 1.4: adding the high-purity terbium carbonate synthetic solution obtained in step 1.3 into a centrifuge while hot, using an 800-mesh filter cloth at 1000 rpm for centrifugation, washing with hot water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate;
[0100] Step 2, preparing high-purity terbium trifluoride;
[0101] Step 2.1 Add 45% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 80° C., add the high-purity terbium carbonate obtained in step 1.4, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 2, heat it to 80° C., stir and react for 3 hours to drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution;
[0102] Step 2.2: The terbium trifluoride synthesis solution is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth to obtain a terbium trifluoride filter cake;
[0103] Step 3, synthesizing potassium terbium decafluoroate;
[0104] Step 3.1: adding electronic grade hydrofluoric acid to a tetrafluoroethylene beaker, and then adding pure water to dilute to a mass fraction of 30%, and then adding high-purity potassium hydroxide thereto, the molar ratio of hydrofluoric acid to potassium hydroxide being 2:1, to obtain a potassium bifluoride solution;
[0105] Step 3.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the potassium bifluoride solution obtained in step 3.1, wherein the molar ratio of potassium bifluoride to terbium trifluoride is 1:3, stirring evenly, heating to 145° C. and evaporating to dryness to obtain a mixed crystal of potassium bifluoride and terbium trifluoride;
[0106] Step 3.3: Add the potassium bifluoride and terbium trifluoride mixed crystal obtained in step 3.2 to an iridium crucible, dry at 220°C for 3 hours, then add to a tubular furnace and dry at 510°C for 2 hours under nitrogen protection, fully dehydrate and fluorinate, and finally heat to 1150°C for 2.5 hours, and perform high temperature reaction under nitrogen protection to remove excess fluoride ions to obtain a finished product of potassium decafluoroterbium oxide. The sample was sent to the Chinese Academy of Sciences for testing, and the test data showed that cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium were all less than 0.5ppm, iron was less than 1ppm, oxygen was less than 0.02%, and the purity reached more than 99.99%, meeting the requirements of crystalline potassium decafluoroterbium oxide.
Claims
1. A method for preparing potassium decafluoroterbium oxide for crystals, characterized in that: The following steps are involved: Step 1, preparing high-purity terbium carbonate; Step 1.1: dissolving high-purity hydrated terbium nitrate crystals with high-purity water to obtain a terbium nitrate solution with a specific gravity of 1.15-1.2, adding the solution to a pure ammonium carbonate solution, adjusting the pH to 8-9, heating to above 80° C., stirring and reacting for 1-2 hours, and obtaining a high-purity terbium carbonate synthetic solution; the high-purity hydrated terbium nitrate crystals are hydrated terbium nitrate crystals with iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents all less than 0.2 ppm; the pure ammonium carbonate solution is an ammonium carbonate solution free of mechanical impurities and trace insolubles, and with iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents all less than 0.1 ppm; Step 1.2: centrifuging the high-purity terbium carbonate synthesis solution while hot, washing with water, controlling the nitrate content to be less than 0.02%, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.3 ppm, to obtain high-purity terbium carbonate; Step 2, preparing high-purity terbium trifluoride; Using electronic grade hydrofluoric acid and the high-purity terbium carbonate to carry out a heat-insulating stirring reaction to drive out carbonate ions to obtain a terbium trifluoride synthetic liquid, and then centrifuging to obtain a terbium trifluoride filter cake; Step 3, synthesizing potassium terbium decafluoroate; Step 3.1: adding the terbium trifluoride filter cake to a high-purity potassium bifluoride solution, stirring evenly, heating to 120-150° C. and evaporating to dryness to obtain a mixed crystal of potassium bifluoride and terbium trifluoride; Step 3.2: drying the potassium bifluoride and terbium trifluoride mixed crystal at 200-250° C. for 3-4 hours, and then drying it at 500-550° C. for 1-2 hours under nitrogen protection to fully dehydrate and fluorinate, and finally heating it to 1100-1200° C. for 2-3 hours to remove excess fluoride ions to obtain a finished potassium decafluoroterbium oxide.
2. The method for preparing crystalline potassium decafluoroterbium according to claim 1, characterized in that: The preparation method of high-purity hydrated terbium nitrate crystals in step 1.1 is specifically as follows: First, analytical pure nitric acid is added to a reaction kettle, and then pure water is added in a ratio of 1:1 to dilute the mixture. Then, high-purity 4N terbium oxide is slowly added thereto, and the molar ratio of nitric acid to terbium is 3:
1. The pH is adjusted to 1-2, the temperature is raised to 60-70° C., and the mixture is stirred for reaction for 30-60 minutes. The supernatant is filtered using a filter element with a filtration accuracy of at least 1 μm to obtain a terbium nitrate solution. Then, the terbium nitrate solution is heated to 110-120° C. and concentrated under slight negative pressure. After a large amount of crystals are concentrated, the solution is stirred and cooled. When the temperature drops to 20-30° C., the crystals are fished out and centrifuged to dry. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, so as to obtain high-purity hydrated terbium nitrate crystals.
3. The method for preparing potassium decafluoroterbium oxide for crystal according to claim 2, characterized in that: The preparation method of the pure ammonium carbonate solution in step 1.1 is specifically as follows: Reagent-grade ammonium carbonate is dissolved in high-purity water to a mass fraction of 15-20%, and filtered to remove mechanical impurities and trace insolubles. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution are controlled to be less than 0.1 ppm to obtain a pure ammonium carbonate solution.
4. The method for preparing potassium decafluoroterbium oxide for crystal according to claim 3, characterized in that: The preparation method of the pure ammonium carbonate solution in step 1.1 is specifically as follows: Reagent-grade ammonium carbonate is dissolved in high-purity water to a mass fraction of 20%, and filtered to remove mechanical impurities and trace insolubles. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium in the ammonium carbonate solution are controlled to be less than 0.1 ppm, and a pure ammonium carbonate solution is obtained.
5. The method for preparing potassium decafluoroterbium oxide for crystal according to any one of claims 1 to 4, characterized in that: In step 1.2, 800 mesh filter cloth is used and centrifugation is performed at a speed of 1000 rpm.
6. The method for preparing potassium decafluoroterbium oxide for crystal according to claim 5, characterized in that: Step 2 is as follows: Step 2.1 Add 40-50% electronic grade hydrofluoric acid by mass to a reaction kettle, heat it to 60-80° C., add the high-purity terbium carbonate obtained in step 1.2, the molar ratio of hydrofluoric acid to terbium is 3:1, adjust the pH to 1-2, heat it to 80° C., stir and react for 2-3 hours to drive out the carbonate ions, and obtain a terbium trifluoride synthesis solution; Step 2.2: The terbium trifluoride synthesis solution is pumped into a centrifuge, and the mixture is centrifuged at 1500 rpm for 30 minutes using a 2000 mesh filter cloth to obtain a terbium trifluoride filter cake.
7. The method for preparing potassium decafluoroterbium oxide for crystal according to claim 6, characterized in that: The step 3.1 is specifically as follows: Step 3.1.1 Add electronic grade hydrofluoric acid into a tetrafluoroethylene beaker, then add pure water to dilute to a mass fraction of 20-30%, add high-purity potassium hydroxide thereto, the molar ratio of hydrofluoric acid to potassium hydroxide being 2:1, to obtain a potassium bifluoride solution; Step 3.1.2: adding the terbium trifluoride filter cake obtained in step 2.2 to the potassium bifluoride solution obtained in step 3.1.1, wherein the molar ratio of potassium bifluoride to terbium trifluoride is 1:3; stirring evenly; heating to 120-150° C. for evaporation to obtain a potassium bifluoride terbium trifluoride mixed crystal.
8. A crystalline potassium decafluoroterbium oxide, characterized in that: The method is prepared by any one of claims 1 to 7.